ANALISIS TERHADAP SISWA YANG BERASAL DARI KELUARGA BROKEN HOME (Studi Kasus di SMK Negeri 2 Gunung Talang) - Tumiyem Tumiyem (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Broken home is a condition that is not harmonious family. One reason for thebroken home because of a divorce between a husband and wife. These conditions affecttheir children, such as lack of affection, do not get proper care and academic failure.However, in the field found a few students who have high academic achievement. Thepurpose of this study is comparing the factors that allow for differences in the academicachievement of children who come from a broken home. The research was conducted inSMK 2 Gunung Talang. The study used form of case studies. Capturing subjects in thisstudy using purposive sampling technique. Analysis of the data using Miles andHuberman interactive model. The conclusion of this study is the difference in academicachievement experienced by students is caused by a broken home: (1) the relationshipwith their parents; students with high achievement have good relationship, studentswith low achievement have not good enough in their relationship, (2) the relationshipwith their teachers; student with high achievement have good relationship, student lowachievement have not good enough in their relationship, (3) the relationship with theirfriends; students with high achievement have good relationship, students with lowachievement have not good enough in their relationship, (4) students attitude tothemselves and family; student with high achievement have good attitude with openbehavior, students with low achievement have introvert behavior, (5) ways of studentslearning; students with high achievement payfull attention on in learning and routineschedule, students with low achievement payless attention to the teachers explanation androutine in learning schedule.Keywords: Analysis, Students, Broken home.PENDAHULUAN